The All-Night Vigil in Early Russian Demestvenny Polyphony (Add. MS 30063 of the British Library) : Presentation of the Critical Edition - Chernova, Elena (Journal of the International Society for Orthodox Music, 2022)
In modern musicology, which studies various polyphonic traditions intensively, it would appear that there are no longer any unknown types of polyphony and undiscovered forms of notating music. The most exotic musical phenomena have been researched and transcribed, and a good many of them have been digitized. Still, one must recognize that the focus of these studies up until now has been predominantly on Western and Central European polyphonic schools, while one significant polyphonic tradition, namely, early Russian polyphony, which, moreover, occupied a fairly extensive historical period, is only now beginning to be investigated systematically. The purpose of this article is to introduce my project involving a critical edition of Russian neumatic polyphony. This edition is the culmination of my work on deciphering neumatic scores of the most festive type of early Russian polyphony—four-part Demestvenny singing (or Demestvo). The object of the present study is the Demestvenny All-Night Vigil recorded in a unique source—a ceremonial illuminated codex belonging to the 17th-century Choir of the Tsar’s and Patriarchal Singing Clerics, which is now kept in the British Library—Add. MS 30063. The edition is planned as part of the dissertation project “The All-Night Vigil in early Russian polyphony,” which I am preparing under the guidance of Professor Dr Christoph Flamm at the Musicology Seminar of the University of Heidelberg. Within its scope, the dissertation examines three types of early Russian polyphony using examples from the All-Night Vigil office. A comprehensive analysis of the hymns themselves will be included in the dissertation but remains outside the scope of this publication.